Immunological Role of the Maternal Uterine Microbiota in Postpartum Hemorrhage - Escobar, Maria F.; Hincapie, Maria A.; Barona, Juan S. (Frontiers in Immunology, 2020)
Recent metagenomics and microbiology studies have identified microorganisms that are typical of the feto-placental unit. Considering this emerging evidence, the placenta, uterus, and the amniotic cavity are not sterile and not immune privileged. However, there is evidence for a beneficial interaction between active maternal immune system and the presence of commensal pathogens, that lead to a an immune tolerant state thereby preventing fetal rejection. Multiple conditions associated with the loss of the normal flora are described (dysbiosis), which could result in perinatal and puerperal adverse events, including, directly or indirectly, postpartum hemorrhage. Altered flora when associated with a severe pro-inflammatory state and combined with patient’s genetic and environmental factors confer a high risk adverse outcome. Better understanding of the adverse role of dysbiosis in pregnancy outcome will improve maternal outcome.